2022
DOI: 10.3390/bioengineering9080403
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and Morphological Characterization of Exserohilum turcicum (Passerini) Leonard and Suggs Causing Northern Corn Leaf Blight of Maize in Bihar

Abstract: Maize is considered the third most important cereal crop in Asia after rice and wheat. Many diseases affect this crop due to the cultivation of various hybrids. This research aimed to characterize the causative agent of northern corn leaf blight disease in Bihar, India, caused by Exserohilum turcicum (Passerini) Leonard and Suggs. Leaf samples were collected from infected fields in five maize growing districts of Bihar in 2020–2022. A total of 45 fungal isolates from 135 samples were examined for cultural, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Several studies conducted by Anwer et al. (2022) and Flora et al. (2023) also indicated that the usage of four genes offering major resistance genes to TLB has been identified and incorporated in many commercial hybrids to tackle the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted by Anwer et al. (2022) and Flora et al. (2023) also indicated that the usage of four genes offering major resistance genes to TLB has been identified and incorporated in many commercial hybrids to tackle the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CLR and TLB management through an integrated disease management that combines host resistance and chemical control strategies in a holistic way rather than using a single component strategy is the best option. It helps farmers improve their overall field management by reducing costs and improving production efficiency on an effective and sustainable basis (Anwer et al., 2022; Carson, 2016; El Khoury & Makkouk, 2010; Shiferaw et al., 2018; Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The recovered isolates varied significantly in morphology including colony color, growth pattern, conidia structures, size, and RMG. Several colony colors of E. turcicum have been reported on PDA: from white to green-white, olivaceous gray to brown with black pigmentation [ 10 , 40 , 41 ]. The range of shades of colony morphology colors observed in the present study were similar to those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most versatile crops having wider adaptability under varied agroecological and climatic conditions. Globally, maize is known as “Queen of Cereals” as it is grown throughout the year due to its photo‐thermo insensitive character and the highest genetic yield potential among the cereals (Anwer et al., 2022; Navarro et al., 2021; Rehab et al., 2019; Romero, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, maize is cultivated in most parts of the country for various purposes, including grain, feed, fodder, green cobs, baby corn, sweet corn, popcorn, and industrial products. In addition to staple food for human being and quality feed for animals, maize serves as a basic raw material as an ingredient to thousands of industrial products that includes starch, oil, protein, alcoholic beverages, food sweeteners, pharmaceutical, cosmetic, film, textile, gum, package, paper industries, and so on (Anwer et al., 2022; ATA, 2014; Gidi, 2023).…”
Section: Introductionmentioning
confidence: 99%